Childhood emotional abuse and adolescent nonsuicidal self-injury: The mediating role of identity confusion and moderating role of rumination. (August 2020) - Gu, Honglei; Ma, Pengyun; Xia, Tiansheng
Abstract: Objective: According to Nock's (2009) integrated model, nonsuicidal self-injury (NSSI) is caused by the interplay of distal environmental and proximal intrapersonal risk factors. Based on this theory, the current study tested a moderated mediation model of family and individual characteristics to investigate how they impact adolescent NSSI. Specifically, we examined whether identity confusion mediated the association between childhood emotional abuse and NSSI, and whether this indirect effect was moderated by rumination. Methods: 949 Chinese adolescents anonymously filled out questionnaires regarding emotional abuse, identity confusion, rumination, and NSSI. Results: The results revealed that childhood emotional abuse was positively associated with NSSI, and this association was mediated by identity confusion. Rumination intensified the association between childhood emotional abuse and identity confusion, as well as the association between childhood emotional abuse and NSSI. Conclusions: These findings highlight the need to consider family and individual factors simultaneously when evaluating risks associated with adolescent NSSI and have important implications for the prevention and intervention of NSSI.